TEACHERS’ BELIEFS ON TEACHER-STUDENTS INTERACTION IN YOUNG LEARNERS’ ENGLISH CLASS - Nernere, Maria Setyaningsih (University of Kuningan, 2019)
Researchers find that teacher plays dominant role in managing the teacher- students interaction, the important aspect affecting the language acquisition process in young learners’ class. Hence, to make sure that the teacher-students interaction goes well for achieving the classroom goals, how the teacher manages the interaction should be investigated further. As beliefs can affect how people act, this research aims to investigate the teachers’ belief on teacher-students interaction in young learners’ English class. This is a qualitative research using direct observation in two English classes at two different Elementary schools and in-depth interview with two English teachers as the data collecting techniques. The data revealed that the teachers’ beliefs affecting how the teacher-students interaction goes consist of beliefs about goals, process, and source of teacher- students interaction. Overall, the interactions were done toachieve two goals namely promoting language acquisition and controlling learning atmosphere. The source of interaction namely teacher talk was adjusted to young learners’ characteristics to make the process of learning meaningful. This finding gives conceptual insight about how the system of teacher-students interaction in English learning process in Elementary schools works. Then, it may be beneficial for the teachers as a means supporting self- reflection, schools’ evaluation and also for the educational practitioners who want to investigate the TSs interaction in more details.